RELEVANCE COMPULSORY LEARNING IN BASIC EDUCATION, PANCASILA STUDENTS AND THE GOLDEN GENERATION OF INDONESIA IN 2045 - Fitri Silvia Sofyan; Aris Riswandi Sanusi (Institut Pendidikan Indonesia, 2023)
This study aims to determine the extent of the relevance between Compulsory Education in Basic Education 12 Years, Pancasila Students, and the 2045 Indonesian Golden Generation. The results of this study indicate that an educational strategy is needed to create the Indonesian Generation towards 2045 as a superior generation. Careful, well-planned strategy and integrated steps for all elements of the nation. In this case basic education is the foundation for seeking to improve the quality of human resources,